2008
DOI: 10.1590/s0102-311x2008000800011
|View full text |Cite
|
Sign up to set email alerts
|

Dor nos dentes e gengivas e fatores associados em adolescentes brasileiros: análise do inquérito nacional de saúde bucal SB-Brasil 2002-2003

Abstract: Estimou-se a prevalência de dor nos dentes e gengivas e fatores associados em adolescentes brasileiros de 15 a 19 anos de idade. Foram utilizadas informações de 16.126 adolescentes participantes do levantamento epidemiológico nacional de saúde bucal - SB Brasil 2002-2003. O desfecho foi o relato de dor nos dentes e gengivas nos últimos seis meses. As variáveis exploratórias foram: renda per capita, escolaridade, condição de estudo, sexo, cor da pele, idade, localização geográfica da residência, tipo de serviço… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
25

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 20 publications
1
17
0
25
Order By: Relevance
“…, 26 The prevalence of dental pain was higher among preschoolers with one or more teeth with caries. This association was to be expected, since pain is one of the symptoms of tooth decay, and was also identified among adolescents5 and adults 9. A previous cohort study, with preschool children aged 5 years in Pelotas (RS - Brazil), observed that individuals with caries had a greater chance (4.8 times) of having dental pain 26.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…, 26 The prevalence of dental pain was higher among preschoolers with one or more teeth with caries. This association was to be expected, since pain is one of the symptoms of tooth decay, and was also identified among adolescents5 and adults 9. A previous cohort study, with preschool children aged 5 years in Pelotas (RS - Brazil), observed that individuals with caries had a greater chance (4.8 times) of having dental pain 26.…”
Section: Discussionmentioning
confidence: 67%
“…- 3 The International Association for the Study of Pain (IASP) defines pain as an unpleasant sensory and emotional experience caused by tissue damage 4. Among the types of orofacial pain, those of dental origin have been reported as the most frequent,5 may affect social interaction, daily activities,6 and may have a negative impact on quality of life 78 It should be noted that the perception of pain may be influenced by knowledge and beliefs of the individuals, as well as by the cultural and social environment in which they live 9…”
Section: Introductionmentioning
confidence: 99%
“…Emergencies of dental origin represent a serious public health problem due to their high prevalence in the population, causing absenteeism, negatively impacting the quality of life and generating high costs related to treatment and use of medicines [6][7][8][9][10]. Often, they are debilitating and can disrupt sleep, work, leisure and interpersonal relationships [11].…”
Section: Introductionmentioning
confidence: 99%
“…Isso é tanto mais relevante quando se constata que, desde 2003 até o início de 2009, foram publicados 27 artigos em periódicos científicos bem qualificados nacional e internacionalmente, os quais utilizaram a base de dados do SB Brasil para estudar diferentes questões de saúde bucal e produzir conhecimento relevante para o planejamento em saúde. Esses trabalhos investigaram, entre outros aspectos, fatores associados à experiência de cárie 13,14,15 , perda dentária e edentulismo 16,17,18 , dor nos dentes e gengivas 19,20 , condições gengivais e doença periodontal 21,22 , autopercepção de saúde bucal 23, 24 , acesso a serviços odontológicos 25,26 , necessidades de tratamento 27,28,29 , acesso à água fluoretada 30,31 . Na comparação com resultados de levantamentos anteriores, foi possível reconhecer e examinar o processo de declínio e polarização da prevalên-cia de cárie no Brasil.…”
Section: Resultados Do Sb Brasil 2003 E Validade Das Inferênciasunclassified